Does central fat distribution reduction after bariatric surgery induce ocular refraction change independent of body mass index? - AKKAYA TURHAN, SEMRA (My University, 2022)
Purpose The effect of body mass index (BMI) and central fat distribution (CFD) reduction after bariatric surgery on ocular refraction is not well established. We assessed association between anthropometric parameters and refraction errors with other ocular and metabolic parameters 1 year after the surgery.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Obesity; Bariatric surgery; Refractive error; Hyperopic shift; Central fat; Laparoscopic sleeve gastrectomy; EYE; HYPERGLYCEMIA; GHRELIN; OBESITY